BaCo0.4Fe0.4Zr0.1Y0.1O3−σ Cathode Performance for Proton Conducting Solid Oxide Fuel Cells with BaZr0.8−xCexY0.1Yb0.1O3−δ Electrolytes - Wenhao Li; Md Shariful Islam Sozal; Vadym Drozd; Andriy Durygin; Zhe Cheng (ECS Advances, 2023)
BaCo _0.4 Fe _0.4 Zr _0.1 Y _0.1 O _3− _σ (BCFZY) is a proton, oxygen-ion, and electron-hole conducting cathode material for intermediate temperature solid oxide fuel cells. Its electrode reaction mechanism in air with moisture is not well understood. In this study, three types of symmetrical cells with the same BCFZY cathode were fabricated over three related proton conducting electrolytes: BaZr _0.8−x Ce _x Y _0.1 Yb _0.1 O _3− _δ (x = 0.1, 0.4, and 0.7). The cathode shows similar performance over three different electrolytes in dry air but different responses to moisture introduction. The differences are hypothesized to relate to the mutual diffusion at the cathode/electrolyte interface. Such a hypothesis is supported by different techniques such as XRD Rietveld refinement of BCFZY cathode in mixtures with different electrolytes after firing, energy-dispersive X-ray spectroscopy (EDS) line scanning for element concentration distribution at the cathode/electrolyte interface, as well as electrochemical test for a related BaCoFeO-type cathode with Zr replaced by Ce.